Hubungan Kompetensi Tutor dan Minat Belajar Siswa Paket B pada Mata Pelajaran Bahasa Indonesia dan Matematika di PKBM Budi Utama Surabaya - Gratia, Emmanuela Sola; Mardliyah, Sjafiatul (J+PLUS UNESA, 2024)
Budi Utama Community Learning Activity Center (PKBM) is one of the non-formal education centers under the Department of Education, Youth, and Sport of Surabaya which runs several programs including equality education such as package A equivalent to elementary school/ MI, package B equivalent to junior high school/ MTS, package C equivalent to high school/ MA. The purpose of this study was to determine the positive relationship between tutor competence and learning interest of package B students in PKBM Budi Utama Surabaya. This study used quantitative methods with data collection used in this study using questionnaires. The results showed that there was no significant relationship between the competence of tutors and the learning interest of package B students in PKBM Budi Utama Surabaya. The results of the data calculation between the tutor's competence in learning Indonesian subjects amounted to 0.723 > 0.05 and in mathematics subjects obtained by 0.320 > 0.05 so from this result it can be concluded that the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted.